2015
DOI: 10.2220/biomedres.36.81
|View full text |Cite
|
Sign up to set email alerts
|

<b>The impact of high-frequency magnetic stimulation of peripheral nerves: muscle hardness, venous blood flow, and motor function of upper extremity in healthy </b><b>subjects </b>

Abstract: The purpose of this study was to investigate the impact of high-frequency peripheral nerve magnetic stimulation on the upper limb function. Twenty-five healthy adults (16 men and 9 women) participated in this study. The radial nerve of the non-dominant hand was stimulated by high-frequency magnetic stimulation device. A total of 600 impulses were applied at a frequency of 20 Hz and intensity of 1.2 resting motor threshold (rMT). At three time points (before, immediately after, and 15 min after stimulation), mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…On the other hand, blood flow velocity and vessel size influence circulatory function, and electrical stimulation also causes physiologic changes by activating sympathetic tone via muscle contraction [28]. In addition, electrical stimulation is effective at reducing the incidence of cardiac vein thrombus and the risk of pulmonary embolism [29] and increases venous return due to increased venous and muscular tension caused by sympathetic tone [30]. By the same electrophysiological mechanisms, high frequency-low intensity sensory stimulation induced vasoconstriction and increased blood flow velocity in this study; thus, it is thought that such stimulation could also enhance normal venous return.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, blood flow velocity and vessel size influence circulatory function, and electrical stimulation also causes physiologic changes by activating sympathetic tone via muscle contraction [28]. In addition, electrical stimulation is effective at reducing the incidence of cardiac vein thrombus and the risk of pulmonary embolism [29] and increases venous return due to increased venous and muscular tension caused by sympathetic tone [30]. By the same electrophysiological mechanisms, high frequency-low intensity sensory stimulation induced vasoconstriction and increased blood flow velocity in this study; thus, it is thought that such stimulation could also enhance normal venous return.…”
Section: Discussionmentioning
confidence: 99%
“…When rPMS is applied to the peripheral nerves, similar effects were also observed in healthy people. Using a pre-post design in normal subjects, Okudera et al (2015) applied 600 magnetic pulses at a frequency of 20 Hz on the radial nerve of the non-dominant hand and showed that the upper limb dexterity performance was improved, which was measured with the Box and Block Test, and this improvement was sustained for at least 15 min. For hand dexterity function change in the present study, the performance of the subjects for the Purdue pegboard improved after one session of rPNMS on the median nerve of the non-dominant hand, and this improvement was exhibited as a latent effect 24 h afterward.…”
Section: Discussionmentioning
confidence: 99%
“…However, FES has some adverse reactions, for example, inducing pain, dermatitis, and even skin burns. In addition, the role of FES is very weak for the deep muscles and nerves, because its stimulating scope is shallow [ 26 , 27 ]. And FES is invalid in chronic hemiplegic patients.…”
Section: Introductionmentioning
confidence: 99%
“…A lot of researches have confirmed the effectiveness of FMS in the aspects of gastric emptying, neurogenic bowel, respiratory muscle conditioning, dysphagia, urinary incontinence, and so on [ 28 32 ]. Okudera et al have confirmed that FMS can improve upper limb motor function in healthy adults [ 27 ]. So we hypothesize that FMS may reduce GHS and promote the recovery of upper limb function in hemiplegic patients.…”
Section: Introductionmentioning
confidence: 99%